The γ'-V2O5 Polymorph as an Attractive 2D Cathodic Material for Lithium and Sodium-Ion Batteries - Baddour-Hadjean, R.; Pereira-Ramos, J.P. (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems, 2018)
Lithium-ion batteries (LIBs) have been the subject of intense research due to their high energy density and good cycling performance. However, considering the low natural occurrence of Li in the upper continental crust (≈ 35 ppm), great concerns have been expressed over whether the available lithium reserves in the earth will be sufficient to meet the ever-growing requirements for LIBs
Keywords: Lithium-ion batteries (LIBs); Na-ion batteries (NIBs)